Ultrasonographic differentiation of bezoar from feces in small bowel obstruction - Kyung Hoon Lee; Hyun Young Han; Hee Jin Kim; Hee Kyung Kim; Moon Soo Lee (Ultrasonography, 2015)
Purpose: To evaluate ultrasonographic accuracy in the differentiation of a bezoar from feces in a small bowel obstruction showing feces-like material just proximal to the transitional zone in abdominal computed tomography (CT). Methods: This study included 14 patients who showed feces-like material just proximal to the transitional zone, among 302 patients diagnosed with small bowel obstruction on abdominal CT. The diagnostic signs of a bezoar on ultrasonography included an arc-like surfaced intraluminal mass, posterior acoustic shadow and twinkling artifacts. The diagnostic performance of ultrasonography in each patient was compared with a final diagnosis that was surgically or clinically made. Results: Among the 14 patients, seven were ultrasonographically diagnosed as having a bezoar, and five of the seven were surgically diagnosed as having a phytobezoar. The remaining two of the seven showed complete symptomatic improvement before surgery. The other seven patients were ultrasonographically diagnosed as not having a bezoar. Among them, six patients were conservatively treated with symptomatic improvement, suggesting the absence of a bezoar. The remaining one patient was confirmed not to have a bezoar during adhesiolysis. In all patients, the ultrasonographic diagnosis agreed with the clinically confirmed diagnosis. Conclusion: Ultrasonography might be an accurate method for the differential diagnosis of feces-like material just proximal to the transitional zone in abdominal CT. It can help radiologists to quickly and easily diagnose a bezoar.